Analisis sajian buku teks pelajaran fisika SMA kelas XI semester 2 terkait komponen contextual teaching and learning (CTL) - Novrizal Saputra; Desnita Desnita; Murtiani Murtiani; Wahyuni Satria Dewi (Universitas Negeri Padang, 2019)
This study aims to determine the presentation of CTL components contained in senior high school phy-sics class XI Semester 2 textbooks. This type of research is a descriptive study using a qualitative approach. The sample used in this study was 4 textbooks which were used by several senior high schools in West Sumatra. Book MK-ER is entitled Physics for Senior High Schools Class XI 2016 written by Marthen Kanginan, the publisher of Erlangga. Book KK-GF titled Active and Creative Student's Study of Physics 2 for Senior High Schools Class XI Specialization in Mathematics and Natural Sciences 2016,written by Ketut Kamajaya, Grafindo publishers. Book MF-TS titled Student Book Study of Physics Concept 2 for Class XI Senior High School Groups Concerning Mathematics and Natural Sciences 2016 written by Muhammad Farchani Rosyid, publisher of the Tiga Serangkai. Book SN-YW titled Physics for Senior High School Class XI Mathematics and Natural Sciences Groups 2016, written by Sunardi, publisher of Yrama Widya. The research instrument used was an analysis sheet containing 7 CTL components and broken down into 39 indicator items. Each indicator is represented by one instrument. Data analysis technique is a content analysis technique by analyzing the contents of written data. The results of this study indicate that the best book in facilitating CTL is book SN-YW-TS with a percentage of fullness of the CTL indicator of 81.5% (very appropriate). The second best book is book KK-GF with a percentage of fulfillment of the CTL indicator of 79.03% (according). Then the third best book is book MF-TS with a percentage of 75.30% (according). While the lowest book in facilitating CTL is book MK-ER with a percentage of 67.83% (quite appropriate). Based on the results of the study, the most recommended book in facilitating CTL used for Senior high school physics class XI is a book written by Sunardi, in 2016, publisher of Yrama Widya.